2012
DOI: 10.2478/v10098-012-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Roughness on the Discharge Coefficient of a Broad-Crested Weir

Abstract: The use of environmentally-friendly materials in hydraulic engineering (e.g. the stone lining of weirs at levees) calls for the more accurate estimation of the discharge coefficient for broad-crested weirs with a rough crest surface. However, in the available literature sources the discharge coefficient of broad-crested weirs is usually expressed for a smooth crest. The authors of this paper have summarized the theoretical knowledge related to the effect of weir crest surface roughness on the discharge coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…• The effect of the weir crest roughness on the discharge coefficient was studied for the set of Nikuradse roughness size k s = 0.014, 0.020 and 0.024 m, for specific discharges varying from q = 0.005 to q = 0.25 m 2 /s, and an upstream slope Z 1 = 2.5, consistently with the study of Pařílková et al (2012). Fig.…”
Section: Numerical Simulationsmentioning
confidence: 63%
See 1 more Smart Citation
“…• The effect of the weir crest roughness on the discharge coefficient was studied for the set of Nikuradse roughness size k s = 0.014, 0.020 and 0.024 m, for specific discharges varying from q = 0.005 to q = 0.25 m 2 /s, and an upstream slope Z 1 = 2.5, consistently with the study of Pařílková et al (2012). Fig.…”
Section: Numerical Simulationsmentioning
confidence: 63%
“…Madadi et al (2014) identified increased discharge coefficient up to 10% with decreasing the upstream face slope from 90 o to 21 o . Pařílková et al (2012) investigated experimentally the influence of the weir surface roughness on the discharge coefficient. For vegetated weir surface conventional flow resistance equations may also be used (Gualtieri et al, 2018).…”
Section: Figmentioning
confidence: 99%
“…(10), C d is deduced as 0.24, smaller than the discharge coefficient of common rectangular weirs (Hager and Schwalt, 1994) and smooth breach (Zhao et al, 2015). This may result from both the initial trapezoid shape of the breach cross section and the large surface roughness which appeared later on the land side (Pařílková et al, 2012).…”
Section: Calculated Results and Analysismentioning
confidence: 99%
“…The amount of the coefficient of the flow in fixed weirs depends on the weir type, shape of the crest (sharp, inclined or rounded) of the upstream entrance (Parílková et al, 2012) and β angle. The amount of the coefficient of the flow in fixed weirs depends on the weir type, shape of the crest (sharp, inclined or rounded) of the upstream entrance (Parílková et al, 2012) and β angle.…”
Section: Water Level Regulation Structures With Fixed Weirmentioning
confidence: 99%